Prevalence, clinical manifestations, laboratory findings, treatment, and outcome of intermediate syndrome in anticholinesterase pesticide intoxication of dogs: A retrospective study. (September 2022) - Klainbart, S.; Kelmer, E.; Chai, O.; Segev, G.; Aroch, I.
Abstract: Organophosphates and carbamates are important anticholinesterase intoxicants of humans and dogs. Intermediate syndrome (IMS) typically occurs 7–96 h following a toxicity-associated acute cholinergic crisis (ACC), and manifests clinically as weakness of the proximal limb, respiratory, and neck flexor muscles. The aim of this study was to describe the prevalence, clinical findings, and outcome of IMS in dogs. The medical records of a veterinary teaching hospital were searched for dogs diagnosed with ACC, IMS, or both, between 2017 and 2021. Case files were retrospectively reviewed. Six historical IMS cases were additionally reviewed. Thirty-two dogs were diagnosed with anticholinesterase intoxication during the search period, of which 23 (72 %) were only diagnosed with ACC, seven (22 %) progressed from ACC to IMS, and two (6 %) were only diagnosed with IMS. Duration of hospitalisation was longer in the IMS group compared to the ACC only group ( P = 0.005). When all dogs with IMS ( n = 15, including the six historical cases) were considered, survival was 100 %, including four (27 %) that required positive pressure mechanical ventilation following respiratory failure. Serum butyrylcholine esterase activity, a marker of cholinesterase activity, was below reference interval when first measured in 14 (93 %) of dogs; however, was not a useful as a recovery marker. IMS should be suspected in dogs demonstrating respiratory, neck, and proximal limb muscle paresis or paralysis, especially following clinical signs consistent with ACC. Absence of clinical signs consistent with ACC or butyrylcholine esterase activity within the reference interval does not exclude IMS as a differential. Highlights: 28 % of dogs with anticholinesterase toxicity developed intermediate syndrome (IMS). Dogs with IMS showed proximal limb, neck flexor, and respiratory muscle weakness. Positive-pressure mechanical ventilation was required by 27 % of dogs with IMS. All dogs with anticholinesterase intoxication-related IMS survived to discharge. Normal butyryl-cholinesterase activities were seen despite persistent IMS-signs.